European perspective on surgical approach in early cervical cancer after LACC trial. An international ESGO survey. (1st November 2019) - Chiva, L; Chacon, E; Carriles, I; Vazquez, D; Platero, M; Castellanos, T; Minguez, J; Gonzalez-Martin, A; Espinos, J; Sanchez, L; Aramendia, JM; Espinosa, I; et al.
Abstract : Introduction/Background: This study aims to understand what was the impact of the LACC trial (Laparoscopy in cervical cancer) among the members of ESGO. We have explored members' understanding of the results and changes in the clinical practice. Methodology: Methods: A questionnaire addressing multiple issues related to the LACC trial and surgical management of early cervical cancer was designed and sent to ESGO members before and after the publication of the LACC trial in the NEJM. The survey was entirely confidentially and could be completed in a short period of time. Responses from 394 and 326 members from 33 European countries were obtained. The respondents were divided into two groups depending on whether or not they belong to European countries. Results: Characteristics and perceptions of the responders are shown in tables 1 and 2 . 97% of responders knew the results of the trial and 92% had read the manuscript. 83% did not expect the results. 56% of members confirmed that have changed their practice after the publication of the trial. Before the trial, only 29% operated cervical cancer by laparotomy and after the publication 63% does. figure 1 and 2 . In cervical cancer patients who have undergone conization with clear margins 73% would offer MIS to the patient while only 49% would if the specimen margins was positive. Members consider that uterine manipulator an incorrect tumor handling occasioned the poorer result of MIS. 9 out 10 of members are willing to discuss the LACC trial with their patients and 80% consider unethical avoiding this discussion. 85% think that ESGO should promote a new randomized clinical trial and meanwhile 65% would be interested to participate in a observational study. Conclusion: Among ESGO members, the publication of LACC trial has objectively modified the surgical approach in early cervical cancer. Disclosure: Nothing to disclose.